Consensus-Oriented Specification System (Journal of Open Law, Technology & Society, 2010)
Pieter Hintjens tells the story of COSS (the Consensus-Oriented Specification System), a toolkit for emerging digital standards. COSS gives workgroups the tools to develop new digital standards with minimum bureaucracy. COSS is a product of the Digital Standard Organization (Digistan), which the FFII open standards workgroup founded with other participants in 2007. In this article he explains why Digistan built COSS and how it works.